The political sociology of human rights - Nash, Kate, 1958- (Cambridge : Cambridge University Press, 2015)
The language of human rights is the most prominent 'people-centred' language of global justice today. This textbook looks at how human rights are constructed at local, national, international and transnational levels and considers commonalities and differences around the world. Through discussions of key debates in the interdisciplinary study of human rights, the book develops its themes by considering examples of human rights advocacy in international organisations, national states and local grassroots movements. Case studies relating to specific organisations and institutions illustrate how human rights are being used to address structural injustices: imperialist geopolitics, authoritarianism and corruption, inequalities created by 'freeing' markets, dangers faced by transnational migrants as a result of the securitization of borders, and violence against women.
Machine generated contents note: 1. The social construction of human rights; 2. (A) human rights movement(s) and other organisations; 3. States of human rights; 4. The United Nations: not a world state; 5. Humanising capitalism; 6. Women's rights are human rights; 7. Do migrants have rights?; 8. What works? Paradoxes in the human rights field.
Title from publisher's bibliographic system (viewed on 30 May 2018).
Keywords: elektronické knihy; electronic books; Human rights -- Social aspects; Political sociology